Psicologia e ontologia: Brentano sobre a unidade da consciência - Valero, Vinicius (2012)
This work consists in the exam of Brentano s account of the unity of consciousness. One can defend that the concept of unity has a crucial role in the argumentative frame of Psychology from an empirical standpoint, published in 1874, and constitute an essential step toward latter investigations in descriptive psychology. Under the concept of unity are centralized psychological and ontological questions that pervade the whole philosopher s work. The assumption of Brentano s mereology, understood as the pure theory of relational properties of psychic parts, is already presented in the work of 1874, where the philosopher reaches his own understanding of consciousness as a complex unity. The influence of these questions in the later descriptive work can also help one to illuminate some controversial points of Brentano s scholarly debate, and insists on the importance of a more comprehensive reading of his work. The complexity of psychic acts is understood as a consequence of the concepts of intentionality and inner perception, a consequence that advance the discussion about the essentially complicated nature of mental structures and the necessity of conceiving psychic phenomena as wholes comprised by parts with different kinds of intimacy. This work defends that it is exactly the solution of this problem that establishes the path for ontology of mental phenomena as relations of parts and wholes encountered in descriptive psychology.